2009
DOI: 10.1088/0031-8949/79/03/035304
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependence of the Judd–Ofelt parameters of Er3 +ions in CaF2crystals

Abstract: In the present study, various concentrations of ErF 3 -doped CaF 2 crystals were grown using the vertical Bridgman method. The Judd-Ofelt intensity parameters t (t = 2, 4, 6) for f-f transitions of Er 3+ ions were determined from optical absorption spectra. The concentration dependence of the intensity parameters radiative transition probability, oscillator strength, branching ratio and radiative lifetime was also investigated. The predicted radiative lifetimes were compared with those of the Er 3+ transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The emission at 321 nm is attributed to transition 2 P 3/2 → 4 I 15/2 . The UV emission at 314 nm, corresponding to the 4 D 5/2 → 4 I 13/2 transition, was observed in Er:CaF 2 crystals [22]. The emission at 321 nm was observed in similar crystals using various excitation techniques, including thermo, radio, X-ray and photoluminescence [14,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emission at 321 nm is attributed to transition 2 P 3/2 → 4 I 15/2 . The UV emission at 314 nm, corresponding to the 4 D 5/2 → 4 I 13/2 transition, was observed in Er:CaF 2 crystals [22]. The emission at 321 nm was observed in similar crystals using various excitation techniques, including thermo, radio, X-ray and photoluminescence [14,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Bitam et al [ 16 ], using the JO method, reported the calculated and experimental radiative lifetime of Er 3+ states and the quantum efficiency in the case of 2 mol% Er 3+ -doped BaF 2 . The JO intensity parameters Ω i (i = 2, 3, 4) for Er 3+ ions of f-f transitions and comparative analysis of the calculated and measured lifetimes were studied by Stef et al [ 9 ] for BaF 2 : 0.2 mol% ErF 3 and by Preda et al [ 22 ] for Er 3+ :CaF 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, the obtained values of the radiative decay times are close to the results of other studies devoted to optical properties of Er 3+ ions in fluoride single crystals and micropowders. 76,[82][83][84] Whereas an acceptable level of conformity between theoretical prediction ( in Table S9) and experimental results ( in Table S6) for the 4 F 9/2 ⟶ 4 I 15/2 transition exists (the relative difference doesn´t exceed 20 % in most ( -)/ cases), for the case of 4 S 3/2 ⟶ 4 I 15/2 and 4 I 13/2 ⟶ 4 I 15/2 transitions a discrepancy between quantum yields extracted from the Judd-Ofelt calculation and the experimental one is significant. The values of estimated via Judd-Ofelt analysis always exceed unity for the 4 I 13/2 ⟶ 4 I 15/2 transition, because measured decay times () are longer than predicted radiative lifetimes ( r ).…”
Section: (8) =mentioning
confidence: 99%
“…where n is the refractive index that should be given at the wavelength of the barycenter of the emission. It can be calculated from the Sellmeier's equation for a given material, which is given in the form [28,29]:…”
Section: Judd-ofelt Theory and Its Relevance For Luminescence Thermometrymentioning
confidence: 99%